Modified superparamagnetic nanocomposite microparticles for highly selective Hg II or Cu II separation and recovery from aqueous solutions - Mandel, Karl; Hutter, Frank; Gellermann, Carsten; Sextl, Gerhard (ACS Applied Materials and Interfaces, 2012)
The synthesis of a reusable, magnetically switchable nanocomposite microparticle, which can be modified to selectively extract and recover Hg II or Cu II from water, is reported. Superparamagnetic iron oxide (magnetite) nanoparticles act as the magnetic component in this system, and these nanoparticles were synthesized in a continuous way, allowing their large-scale production. A new process was used to create a silica matrix, confining the magnetite nanoparticles using a cheap silica source [sodium silicate (water glass)]. This results in a well-defined, filigree micrometer-sized nanocomposite via a fast, simple, inexpensive, and upscalable process. Hence, because of the ideal size of the resulting microparticles and their comparably large magnetization, particle extraction from fluids by low-cost magnets is achieved. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2020-04-02
Keywords: microparticle; nanocomposite; recycling; separation; superparamagnetism